Pemanfaatan Plugin After Effect Untuk Produksi Film - Supriyadi Supriyadi (Universitas Bina Sarana Informatika, 2019)
Abstract - Film is a communication media that is audio visual in nature to convey a message to a group of people who gather in a certain place. Movie messages on mass communication can take the form of anything depending on the film's mission. However, generally a film can include a variety of messages, both messages of education, entertainment and information. The message in the film is to use the mechanism of symbols that exist in the human mind in the form of message content, voice, words, conversations and so on. Trailer is a preview or excerpts of interesting scenes from a film, which aims to attract the audience to want to see the film that is. While the development of the world of film itself in recent years is very rapidly advancing. Lots of interesting scenes that are very extraordinary are shown on some of the leading films in the world today. Like the trailer on Aquaman and Avenger's films, wherein there are scenes showing an engineering city that resembles the original in the story and explosions that destroy buildings or the surrounding environment. It is impossible for such places to exist on this earth. The making of special effects as in the scenes will later use the technique of implementing essential elements in footage movie action in Adobe After Effect and several plugins that support it. At the end of the project it will produce a trailer, where later the processing techniques can inspire young Indonesian filmmakers as learning media in the field of film. It can also be used as a new method for re-processing an event that is not possible by directly reconstructing it using ordinary video